Penerapan Metode Economic Order Quantity dalam Pengendalian Bahan Pendukung Produksi pada Part N01072 di PT. F - Arifin, Fathul; Winarno, Winarno (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. F is a company operating in the automotive sector with products produced in the form of spare parts for cars and motorbikes. The problem faced by this company is the order made by the company when purchasing production-supporting materials which results in excess production-supporting materials, especially oil, this will result in high storage costs for the production-supporting materials and the company will incur additional costs for these expenses. The methods used to control production support materials are Economic Order Quantity (EOQ) and forecasting methods. For the quantity ordered for production support materials, after calculating using the probabilistic model EOQ method, it was found that it was 28 liters of oil per order in the period February 2023 to December 2023. In addition, the company can find out the reorder point and safety stock for the production support materials, each of which is 47 liters. and 41 liters, so that companies are better able to control oil supplies and the problem of excess/shortage of production support materials will not recur. Keywords: Economic Order Quantity (EOQ), Forecasting, Production Support Materials,  Supply